(untitled) (Semiárida, 2020)
The aim of this report is to show data about the content of equivalent of tannic acid, raw protein, weight of one thousand grains and possible co-relations in 54 hybrids of grainy sorghum cultivated in the semiarid "pampeana" region. The results obtained on material sowed during the 80/81 period in the Experimental Field of the "Facultad de Agronomía" of de UNLPam. are presented here. A highly meaningful co-relation, between the weight of one thousand grains and the equivalent percentage in tannic acid detected; no co-relation between the tannic nature and the raw protein was obtained.